Botrytis cinerea in raspberry in Serbia I: Morphological and molecular characterization - Tanović, Brankica Borko; Hrustić, Jovana; Mihajlović, Milica; Grahovac, Mila; Delibašić, Goran (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2015)
Morphological and molecular characterisation of 130 isolates of Botrytis cinerea, derived from raspberry fruit originating from six commercial fields in a raspberry growing region of Serbia (locations: Požega, Prilike, Arilje, Ivanjica, Šabac and Valjevo) was performed. The results showed that all isolates formed white, uniform, aerial mycelia with entire margin on PDA medium. First morphological differences among the isolates appeared after six days of incubation. Three-week old isolates were grouped into eight distinct morphological types – four mycelial and four sclerotial. Mostly, they were of sclerotial type (81.5%) and the most frequently found was an S3 type, which formed large irregularly placed sclerotia. This type was dominant in five of six investigated locations and represented 45-65% of the isolates. The least frequent was the mycelial type M3 (0.7% of the isolates) characterized by mycelial masses. The presence of Boty and/or Flipper transposons was detected in isolates originating from all investigated locations. It was discovered that the B. cinerea population in raspberry in Serbia, besides the well-described genetically isolated sympatric species transposa (43.1%) and vacuma (10.8%), contains also another two, boty (44.6%) and flipper (1.5%) species with only one transposon (either Boty or Flipper) in the genome. In addition, it was revealed that all isolates from raspberry collected in Serbia, transposa, vacuma, boty or flipper, are sensitive or weakly resistant to fenhexamid and therefore belong to the B. cinerea genetical Group II.